2021
DOI: 10.1177/17479541211020452
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between the overhead press and split jerk maximum performance? Influence of sex

Abstract: The aims of this study were to (I) determine the differences and relationship between the overhead press and split jerk performance in athletes involved in weightlifting training, and (II) explore the magnitude of these differences in one-repetition maximum (1RM) performances between sexes. Sixty-one men (age: 30.4 ± 6.7 years; height: 1.8 ± 0.5 m; body mass 82.5 ± 8.5 kg; weightlifting training experience: 3.7 ± 3.5 yrs) and 21 women (age: 29.5 ± 5.2 yrs; height: 1.7 ± 0.5 m; body mass: 62.6 ± 5.7 kg; weightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 23 publications
0
22
2
Order By: Relevance
“…In addition, the R 2 was very high (0.94) and the S E low (4.62), suggesting that back squat and overhead press performances can explain 94% of the variance in SJ performance, in competitive weightlifters, accurately (Figure 1). These findings are slightly different compared with previous results, where Soriano et al (16) reported a lower coefficient of determination between the overhead press and SJ performance for men ( R 2 = 0.81). Likely, differences between these findings are attributed to the addition of the lower-body dynamic strength to the prediction equation.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, the R 2 was very high (0.94) and the S E low (4.62), suggesting that back squat and overhead press performances can explain 94% of the variance in SJ performance, in competitive weightlifters, accurately (Figure 1). These findings are slightly different compared with previous results, where Soriano et al (16) reported a lower coefficient of determination between the overhead press and SJ performance for men ( R 2 = 0.81). Likely, differences between these findings are attributed to the addition of the lower-body dynamic strength to the prediction equation.…”
Section: Discussioncontrasting
confidence: 97%
“…The results obtained in this study show weaker correlations between foundation strength (overhead press and front squat) and weightlifting (clean and jerk and snatch) exercises compared with the studies of Lucero et al (16), Soriano et al (29), and Stone et al (35). These authors reported high to almost perfect correlations between foundation strength exercises (overhead press, back squat, and front squat) and snatch and clean and jerk performance ( r -range: 0.83–0.94).…”
Section: Discussioncontrasting
confidence: 96%
“…In this study, the explained variance in the absolute and relative strength performance in the overhead press was moderately related to performance in the snatch and clean and jerk (48–46%, 44–41%, respectively). Soriano et al (29) offer an interesting insight into the relationship between the jerk and the overhead press exercises. The authors reported high correlations between these movements ( r = 0.83).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations